Periodic hypokalaemic polymyopathy in Burmese and closely related cats: A review including the latest genetic data. Issue 5 (May 2015) - Malik, Richard; Musca, Fran J; Gunew, Marcus N; Menrath, Victor H; Simpson, Christopher; Culvenor, John; Grahn, Robert A; Helps, Christopher; Lyons, Leslie A; Gandolfi, Barbara
Global importance: Hypokalaemic polymyopathy is a genetic disease of Burmese cats that has been encountered in Australasia, Europe and South Africa. Clinical features: Affected cats usually present with signs of muscle weakness and muscle pain in the first year of life. Although certain clinical features, such as ventroflexion of the head and neck, are especially characteristic, some cats do not display these signs. Usually weakness is periodic or episodic, but occasionally it is incessant. Diagnostic challenges: In the past, diagnosis was problematic in that clinical signs and a lowered serum potassium concentration were not always observed synchronously. This necessitated serial serum potassium concentration determinations, testing of serum creatine kinase activity and exclusion of other potential causes of muscle disease in cats (including muscular dystrophies, Toxoplasma myositis, immune-mediated polymyositis, organophosphorus intoxication and envenomations). Signs in affected cats often waxed and waned, possibly in response to changes in dietary factors and stress, and some cats could apparently 'grow out of' the condition. Recent advances and future prospects: Recent molecular genetics research has identified a single nonsense mutation in the gene ( WNK4 ) coding for lysine-deficient 4 protein kinase, an enzyme present primarily in the distal nephron. The underlying pathomechanism in affected cats is therefore likely to be a potassium wasting nephropathy, as this enzyme is involved in complex sodium/potassium exchange mechanisms in the kidney. Additional functional characterisation of the condition is warranted to define precisely how, why and when the serum potassium concentration declines. The diagnosis of Burmese hypokalaemia is now straightforward, as an inexpensive PCR test can identify affected homozygous individuals, as well as carriers. The elimination of this condition from the Burmese breed, and also from pedigree cats infused with Burmese lines, such as the Bombay, Tonkinese and Tiffanie breeds, should therefore be possible.